2011
DOI: 10.1128/aem.00536-11
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Detection and Identification of Chlamydophila Species in Veterinary Specimens by Using SYBR Green-Based PCR Assays

Abstract: Infections caused by members of the Chlamydiaceae family have long been underestimated due to the requirement of special laboratory facilities for the detection of this group of intracellular pathogens. Furthermore, new studies of this group of intracellular pathogens have revealed that host specificity of different species is not as clear as recently believed. As most members of the genus Chlamydophila have shown to be transmissible from animals to humans, sensitive and fast detection methods are required. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…For the detection of Chlamydiaceae species in the eye swabs lysates, an SYBR green-based qPCR assay was performed using the primers Chuni-1F and Chuni-2R. 31 Each reaction consisted of 2.5 µl of DNA sample, 12.5 µl of SYBRGreen PCR Master Mix 2x (Applied Biosystems, Warrington, UK), 400nM of each forward and reverse primer and nuclease-free water to a total volume of 25 µl. PCR was performed following reported cycling conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the detection of Chlamydiaceae species in the eye swabs lysates, an SYBR green-based qPCR assay was performed using the primers Chuni-1F and Chuni-2R. 31 Each reaction consisted of 2.5 µl of DNA sample, 12.5 µl of SYBRGreen PCR Master Mix 2x (Applied Biosystems, Warrington, UK), 400nM of each forward and reverse primer and nuclease-free water to a total volume of 25 µl. PCR was performed following reported cycling conditions.…”
Section: Methodsmentioning
confidence: 99%
“…PCR was performed following reported cycling conditions. 31 Samples were assayed per duplicate and were assayed with an exogenous Internal Positive Control (IPC; Applied Biosystems, USA) to detect eventual PCR inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…However, given the conservation of bacterial 16S rRNA genes, it is challenging, if not impossible, to design primers for targeting specific strains, thereby hampering the rapid detection of disease-discriminatory taxa. Instead, a few studies have designed 16S rRNA gene-targeted group-specific primers for rapidly detecting the dominant gut bacterial phyla (15,17,18). Based on these studies, age-discriminatory phyla, Alphaproteobacteria and Verrucomicrobia, were first identified.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations impede its use in routine monitoring applications. In this regard, cheap, rapid, and convenient features of quantitative PCR (qPCR) might overcome these shortcomings (15). Indeed, qPCR is being used to detect the dominant gut bacterial lineages in human (16) and pig (17).…”
mentioning
confidence: 99%
“…Detection of Campylobacter was based on amplification of a DNA segment within the flaA short variable region (SVR) of Campylobacter jejuni or C. coli, according to Ridley et al [47]. Chlamydia detection centred on amplifying the IGS region and domain I of 23S rRNA gene, following Nordentoft et al [48]. Salmonella detection used primers specific for the invA gene, as described by Rahn et al [49].…”
Section: Bacteria Sampling and Laboratory Diagnosismentioning
confidence: 99%